Reinforcement film, manufacturing method of device and reinforcement method

JP2025025974APending Publication Date: 2025-02-21NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023131279
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0018】 本発明の補強フィルムは、粘着剤層が光硬化性組成物からなり、被着体との接着後に粘着剤層を光硬化することにより、被着体との接着力が上昇する。粘着剤層は、光硬化前は、表面活性化処理された被着体に対しても接着力が小さく、被着体からのはく離が容易である。光硬化後の粘着剤は高温においても高い接着力を有し、接着信頼性に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025974000001_ABST
    Figure 2025025974000001_ABST
Patent Text Reader

Abstract

To provide a reinforcement film easy to separate from an adherend immediately after bonding thereof, capable of strongly bonding with the adherend through photocuring an adhesive agent after bonding with the adherend, while exhibiting a high adhesive force even under a high temperature environment.SOLUTION: A reinforcement film (10) includes an adhesive layer (2) fastened and laminated on a principal plane of a film base material (1). The adhesive layer includes a photocurable composition including an acrylic base polymer having a cross-linking structure, a photocuring agent, and a photoinitiator. The acrylic base polymer includes, as a monomer component, one or more selected from a group including a hydroxy group-containing monomer and a carboxy group-containing monomer, and a nitrogen atom-containing monomer. The photocurable composition includes, as the photocuring agent, a polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond and a urethane (meth)acrylate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reinforced film in which a film substrate and a photocurable pressure-sensitive adhesive layer are bonded to each other. The present invention also relates to a method for producing a device having a surface to which the reinforced film is bonded, and a reinforcing method for bonding the reinforced film to the surface of an adherend. [Background technology]

[0002] An adhesive film may be attached to the surface of an optical device such as a display or an electronic device for the purpose of surface protection, imparting impact resistance, etc. Such an adhesive film usually has an adhesive layer fixedly laminated on the main surface of a film substrate, and is attached to the device surface via this adhesive layer.

[0003] By temporarily attaching an adhesive film to the surface of a device or a device component before use, such as during device assembly, processing, transportation, etc., it is possible to prevent the adherend from being scratched or damaged. Patent Document 1 discloses a reinforcing film provided on a film substrate with a photocurable adhesive layer containing an acrylic-based polymer, a multifunctional (meth)acrylate as a photocuring agent, and a photopolymerization initiator.

[0004] This reinforcing film has low adhesion immediately after being attached to the adherend, so it can be easily peeled off from the adherend. This allows reworking from the adherend, and also allows the reinforcing film to be selectively peeled off from areas of the adherend that do not require reinforcement. The adhesive of the reinforcing film firmly adheres to the adherend by photocuring, so the film base material is permanently bonded to the surface of the adherend, and it can be used as a reinforcing material for protecting the surface of devices. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-132846 A Summary of the Invention [Problem to be solved by the invention]

[0006] Before bonding a reinforcing film to the surface of an adherend such as a device, a surface activation treatment such as plasma treatment or corona treatment may be performed for the purpose of cleaning the adherend surface, etc. When a reinforcing film is bonded to the surface of an adherend after the surface activation treatment, the adhesive strength is higher than when the reinforcing film is bonded to an adherend that has not been subjected to the surface activation treatment, and peeling of the reinforcing film from the adherend may be difficult.

[0007] Patent Document 1 describes that since the acrylic base polymer constituting the photocurable adhesive does not contain nitrogen atoms, even if the surface of the adherend is activated, the adhesive strength to the adherend is low, the reinforcing film is easy to peel off, and the adhesive strength increases when the adhesive is photocured. However, the reinforcing film in Patent Document 1 has low adhesive strength at high temperatures after photocuring, and the adhesive reliability is insufficient.

[0008] In view of these problems, the present invention aims to provide a reinforcing film that has low adhesion to an adherend and is easy to peel off before the adhesive is photo-cured, even if the surface of the adherend has been activated with plasma or the like, and that has high adhesion at high temperatures and excellent adhesive reliability after the adhesive is photo-cured. [Means for solving the problem]

[0009] The reinforcing film of the present invention includes a pressure-sensitive adhesive layer fixedly laminated on one main surface of a film substrate, the pressure-sensitive adhesive layer being made of a photocurable composition containing an acrylic-based polymer having a crosslinked structure, a photocuring agent, and a photopolymerization initiator.

[0010] The acrylic base polymer contains, as monomer components, at least one selected from the group consisting of hydroxyl group-containing monomers and carboxyl group-containing monomers, and a nitrogen atom-containing monomer. The content of the nitrogen atom-containing monomer relative to 100 parts by weight of the total amount of the monomer components of the acrylic base polymer is preferably 0.3 to 10 parts by weight.

[0011] The acrylic base polymer preferably has a crosslinked structure introduced therein using 0.05 to 1.0 parts by weight of a crosslinking agent relative to 100 parts by weight of the polymer. Examples of the crosslinking agent include isocyanate-based crosslinking agents and epoxy-based crosslinking agents.

[0012] The photocurable composition constituting the pressure-sensitive adhesive layer contains, as a photocuring agent, a polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond, and a urethane (meth)acrylate. The amount of the polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond is preferably 3 to 30 parts by weight relative to 100 parts by weight of the acrylic base polymer. The amount of the urethane (meth)acrylate is preferably 0.03 to 5 parts by weight relative to 100 parts by weight of the acrylic base polymer.

[0013] The polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond may have a functional group equivalent of a (meth)acryloyl group of 80 to 500 g / eq. The urethane (meth)acrylate may have a functional group equivalent of a (meth)acryloyl group of 80 to 5000 g / eq. The urethane (meth)acrylate may have four or more (meth)acryloyl groups in one molecule.

[0014] Before photocuring, the adhesive layer preferably has an adhesive strength F0 to a polyimide film at 25° C. of 0.4 N / 25 mm or less, and an adhesive strength F1 to a plasma-treated polyimide film at 25° C. of 1.4 times F0 or less. F1 is preferably 0.5 N / 25 mm or less.

[0015] The pressure-sensitive adhesive layer, after photocuring, preferably has an adhesive strength F2 of 3.0 N / 25 mm or more at 25° C. and an adhesive strength F3 of 1.0 N / 25 mm or more at 85° C. to a plasma-treated polyimide film. The pressure-sensitive adhesive layer, after photocuring, preferably has a shear storage modulus of 150 kPa or less at 25° C.

[0016] The above-mentioned reinforcing film is attached temporarily to the surface of the device as the adherend, and then the adhesive layer is photocured to obtain a device with the reinforcing film. The device may be a foldable flexible device, and the adherend (reinforcement target) of the reinforcing film may be a foldable image display element. The adherend may include a polyimide film.

[0017] Before the reinforcing film is temporarily attached, the surface of the adherend may be subjected to an activation treatment such as a plasma treatment. After the reinforcing film is temporarily attached to the adherend, and before the pressure-sensitive adhesive layer is photocured, the reinforcing film temporarily attached to the adherend may be cut, and the reinforcing film may be peeled off and removed from a portion of the adherend (a non-reinforced area). Effect of the Invention

[0018] The reinforcing film of the present invention has an adhesive layer made of a photocurable composition, and the adhesive layer is photocured after adhesion to an adherend, thereby increasing the adhesive strength with the adherend. Before photocuring, the adhesive layer has low adhesive strength even to an adherend that has been surface-activated, and is easy to peel from the adherend. After photocuring, the adhesive has high adhesive strength even at high temperatures and has excellent adhesive reliability. [Brief description of the drawings]

[0019] [Figure 1] FIG. 2 is a cross-sectional view showing a laminated structure of a reinforcing film. [Diagram 2] FIG. 2 is a cross-sectional view showing a laminated structure of a reinforcing film. [Diagram 3] FIG. 2 is a cross-sectional view showing a device to which a reinforcing film is attached. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] 1 is a cross-sectional view showing one embodiment of a reinforced film. The reinforced film 10 has a pressure-sensitive adhesive layer 2 on one main surface of a film substrate 1. The pressure-sensitive adhesive layer 2 is fixedly laminated on one main surface of the film substrate 1. The pressure-sensitive adhesive layer 2 is a photocurable pressure-sensitive adhesive made of a photocurable composition, and is cured by irradiation with active light such as ultraviolet light, thereby increasing the adhesive strength with an adherend.

[0021] Fig. 2 is a cross-sectional view of a reinforced film having a release liner 5 temporarily attached onto the main surface of a pressure-sensitive adhesive layer 2. Fig. 3 is a cross-sectional view showing a state in which a reinforced film 10 is attached to the surface of a device 20.

[0022] The release liner 5 is peeled off and removed from the surface of the adhesive layer 2, and the exposed surface of the adhesive layer 2 is attached to the surface of the device 20, thereby attaching the reinforcement film 10 to the surface of the device 20. In this state, the adhesive layer 2 has not yet been photocured, and the reinforcement film 10 (adhesive layer 2) is temporarily attached onto the device 20. By photocuring the adhesive layer 2, the adhesive strength at the interface between the device 20 and the adhesive layer 2 increases, and the device 20 and the reinforcement film 10 are fixed together.

[0023] "Fixed" means that the two laminated layers are firmly bonded together, making it difficult or impossible to peel them apart at their interface. "Temporary" means that the adhesive strength between the two laminated layers is weak, making them easy to peel apart at their interface.

[0024] In the reinforced film shown in Figure 2, film substrate 1 and adhesive layer 2 are bonded together, and release liner 5 is temporarily attached to adhesive layer 2. When film substrate 1 and release liner 5 are peeled away from each other, peeling occurs at the interface between adhesive layer 2 and release liner 5, and the adhesive layer 2 remains bonded to film substrate 1. No adhesive remains on release liner 5 after peeling.

[0025] In the device with the reinforcement film 10 attached as shown in FIG. 3, the device 20 and the adhesive layer 2 are in a temporary bonded state before the adhesive layer 2 is photocured. When the film substrate 1 is peeled off from the device 20, peeling occurs at the interface between the adhesive layer 2 and the device 20, and the adhesive layer 2 remains fixed on the film substrate 1. Since no adhesive remains on the device 20, rework is easy. After the adhesive layer 2 is photocured, the adhesive strength between the adhesive layer 2 and the device 20 increases, so it is difficult to peel the reinforcement film 10 from the device 20, and peeling the two may cause cohesive failure of the adhesive layer 2.

[0026] [Structure of the reinforcing film] <Film substrate> A plastic film is used as the film substrate 1. In order to bond the film substrate 1 and the pressure-sensitive adhesive layer 2, it is preferable that the surface of the film substrate 1 to which the pressure-sensitive adhesive layer 2 is to be attached has not been subjected to a release treatment.

[0027] The thickness of the film substrate 1 is, for example, about 4 to 500 μm. From the viewpoint of reinforcing the device by imparting rigidity and cushioning impact, the thickness of the film substrate 1 is preferably 12 μm or more, more preferably 30 μm or more, and even more preferably 45 μm or more. From the viewpoint of imparting flexibility to the reinforcing film to enhance handleability, the thickness of the film substrate 1 is preferably 300 μm or less, and more preferably 200 μm or less. To impart flexibility to the reinforcing film to make it foldable, the thickness of the film substrate 1 is preferably 125 μm or less, and more preferably 100 μm or less. From the viewpoint of achieving both mechanical strength and flexibility, the compressive strength of the film substrate 1 is 100 to 3000 kg / cm 2 is preferable, and 200 to 2900 kg / cm 2 More preferably, 300 to 2800 kg / cm 2 More preferably, 400 to 2700 kg / cm 2 is particularly preferred.

[0028] Examples of plastic materials constituting the film substrate 1 include polyester resins, polyolefin resins, cyclic polyolefin resins, polyamide resins, polyimide resins, polyether ether ketone resins, and the like. In a reinforcing film for an optical device such as a display, the film substrate 1 is preferably a transparent film. In addition, when the photocuring of the adhesive layer 2 is performed by irradiating active light from the film substrate 1 side, the film substrate 1 is preferably transparent to the active light used for curing the adhesive layer. Since it has both mechanical strength and transparency, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferably used. When the adhesive layer is cured by irradiating active light from the adherend side, it is sufficient that the adherend has transparency to active light, and the film substrate 1 does not need to be transparent to active light.

[0029] The surface of the film substrate 1 may be provided with a functional coating such as an easy-adhesion layer, an easy-slip layer, a release layer, an antistatic layer, a hard coat layer, an antireflection layer, etc. As described above, in order to bond the film substrate 1 and the pressure-sensitive adhesive layer 2, it is preferable that no release layer is provided on the surface of the film substrate 1 to which the pressure-sensitive adhesive layer 2 is to be attached.

[0030] <Adhesive layer> The adhesive layer 2, which is fixedly laminated on the film substrate 1, is made of a photocurable composition containing a base polymer, a photocuring agent, and a photopolymerization initiator. The adhesive layer 2 has low adhesive strength with adherends such as devices and device parts before photocuring, and is therefore easy to peel off. The adhesive layer 2 has improved adhesive strength with adherends due to photocuring, so the reinforcing film is unlikely to peel off from the device surface even when the device is in use, and has excellent adhesive reliability.

[0031] The photocurable pressure-sensitive adhesive hardly cures in a general storage environment, but cures when exposed to actinic rays such as ultraviolet rays. Therefore, the reinforcing film of the present invention has the advantage that the timing of curing the pressure-sensitive adhesive layer 2 can be set arbitrarily, and the process lead time can be flexibly accommodated.

[0032] The thickness of the pressure-sensitive adhesive layer 2 is, for example, about 1 to 300 μm. The thicker the pressure-sensitive adhesive layer 2, the more the adhesiveness to the adherend tends to improve. On the other hand, if the pressure-sensitive adhesive layer 2 is too thick, the fluidity before photocuring is high, and handling may become difficult. Therefore, the thickness of the pressure-sensitive adhesive layer 2 is preferably 3 to 100 μm, more preferably 5 to 50 μm, further preferably 6 to 40 μm, and particularly preferably 8 to 30 μm. From the viewpoint of thinning, the thickness of the pressure-sensitive adhesive layer 2 may be 25 μm or less, 20 μm or less, or 18 μm or less.

[0033] When the reinforcing film is used in an optical device such as a display, the total light transmittance of the pressure-sensitive adhesive layer 2 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The haze of the pressure-sensitive adhesive layer 2 is preferably 2% or less, more preferably 1% or less, even more preferably 0.7% or less, and particularly preferably 0.5% or less.

[0034] In the following, preferred embodiments of each component of the photocurable composition constituting the pressure-sensitive adhesive layer 2 will be described in order.

[0035] (Base polymer) The base polymer is the main component of the pressure-sensitive adhesive composition and is the main factor that determines the adhesive strength of the pressure-sensitive adhesive layer. The pressure-sensitive adhesive composition contains an acrylic polymer as the base polymer. It is preferable that 50% by weight or more of the pressure-sensitive adhesive composition is an acrylic polymer. The acrylic base polymer is excellent in optical transparency and adhesiveness, and the adhesive strength can be easily controlled.

[0036] The acrylic polymer preferably contains an alkyl (meth)acrylate ester as a main monomer component. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.

[0037] As the (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 is preferably used. The (meth)acrylic acid alkyl ester may have an alkyl group that is branched, or may have a cyclic alkyl group (alicyclic alkyl group).

[0038] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and (meth) Examples of the acrylate include nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.

[0039] Specific examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylic acid esters having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. The (meth)acrylic acid alkyl ester having an alicyclic alkyl group may have a substituent on the ring such as 3,3,5-trimethylcyclohexyl (meth)acrylate. The (meth)acrylic acid alkyl ester having an alicyclic alkyl group may be a (meth)acrylic acid ester containing a condensed ring of an alicyclic structure and a ring structure having an unsaturated bond, such as dicyclopentenyl (meth)acrylate.

[0040] The content of the (meth)acrylic acid alkyl ester is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and may be 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more, relative to 100 parts by weight of the total amount of the monomer components constituting the polymer.

[0041] From the viewpoint of lowering the glass transition temperature (Tg) of the acrylic base polymer and increasing the adhesive strength over a wide temperature range, the alkyl group of the (meth)acrylic acid alkyl ester is preferably a chain alkyl group. The chain alkyl group may be linear or branched.

[0042] Among the exemplified (meth)acrylic acid alkyl esters, from the viewpoint of lowering the Tg of the base polymer, (meth)acrylic acid C having an alkyl group with 1 to 9 carbon atoms is preferred. 1-9The (meth)acrylic acid alkyl ester is preferably one having a homopolymer glass transition temperature of -50°C or lower. Among them, (meth)acrylic acid alkyl esters having an alkyl group with 6 to 9 carbon atoms are preferred. 6-9 Alkyl esters are preferred.

[0043] (Meth)acrylic acid C, the homopolymer of which has a glass transition temperature of -50°C or lower 6-9 Specific examples of alkyl esters include 2-ethylhexyl acrylate (Tg: -70°C), n-hexyl acrylate (Tg: -65°C), n-octyl acrylate (Tg: -65°C), isononyl acrylate (Tg: -60°C), n-nonyl acrylate (Tg: -58°C), isooctyl acrylate (Tg: -58°C), etc. Among these, 2-ethylhexyl acrylate and n-octyl acrylate are preferred because they have a low Tg and can reduce the storage modulus of the adhesive.

[0044] In acrylic-based polymers, the monomer (main monomer) with the highest content among the constituent monomers is (meth)acrylic acid C. 6-9 It is preferably an alkyl ester. 6-9 The amount of alkyl ester is preferably 40 parts by weight or more, more preferably 50 parts by weight or more, and may be 55 parts by weight or more, 60 parts by weight or more, or 65 parts by weight or more, based on 100 parts by weight of the total amount of the constituent monomer components of the polymer.

[0045] The acrylic base polymer may contain two or more (meth)acrylic acid alkyl esters as monomer components, and (meth)acrylic acid C 1-9 Alkyl esters and (meth)acrylic acid C 10-20 A homopolymer of a (meth)acrylic acid alkyl ester having a long-chain alkyl group having 10 or more carbon atoms has a temperature region (plateau region) above Tg where the viscoelasticity has little temperature dependence. Therefore, when the base polymer contains (meth)acrylic acid C as a monomer component, 10-20By including an alkyl ester, the temperature dependence of the storage modulus becomes smaller, and warping of the adherend caused by temperature changes and peeling of the reinforcing film from the adherend may be suppressed.

[0046] Since the temperature range of the plateau region is wide and the storage modulus in the plateau region is small, (meth)acrylic acid C 10-20 Among the chain alkyl esters, (meth)acrylic acid C 12-18 Alkyl esters are preferred. Among them, dodecyl (meth)acrylate and isostearyl (meth)acrylate are preferred, and dodecyl acrylate (lauryl acrylate) is particularly preferred.

[0047] The acrylic base polymer contains (meth)acrylic acid C as a monomer component. 10-20 If it contains an alkyl ester, (meth)acrylic acid C 10-20 The amount of the alkyl ester is preferably 1 to 40 parts by weight, more preferably 2 to 30 parts by weight, and further preferably 3 to 25 parts by weight, and may be 4 to 20 parts by weight or 5 to 15 parts by weight, relative to 100 parts by weight of the total amount of the constituent monomer components of the polymer.

[0048] The acrylic base polymer contains, as a constituent monomer component, a hydroxyl group-containing monomer and / or a carboxyl group-containing monomer in addition to a (meth)acrylic acid alkyl ester. The hydroxyl group or carboxyl group of the base polymer becomes a reaction site with a crosslinking agent described below. For example, when an isocyanate-based crosslinking agent is used, it is preferable that the monomer component of the base polymer contains a hydroxyl group-containing monomer. When an epoxy-based crosslinking agent is used, it is preferable that the monomer component of the base polymer contains a carboxyl group-containing monomer. The introduction of a crosslinked structure into the base polymer improves the cohesive force, and tends to improve the peelability of the pressure-sensitive adhesive layer 2 from the adherend before photocuring.

[0049] Examples of hydroxy group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate, etc. Among these, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are preferred because they contribute greatly to improving the adhesive strength of the adhesive after photocuring.

[0050] Examples of the carboxy group-containing monomer include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred, since the adhesive strength and adhesive retention are likely to be improved due to the increased cohesiveness of the adhesive.

[0051] From the viewpoint of appropriately introducing a crosslinked structure by a crosslinking agent such as an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent, the total amount of the hydroxy group-containing monomer and the carboxy group-containing monomer relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more, or 1.0 part by weight or more.

[0052] Since hydroxyl groups and carboxyl groups are highly polar, when the amount of hydroxyl group-containing monomer or carboxyl group-containing monomer in the constituent monomer components of the acrylic base polymer is large, the cohesive force of the polymer increases, and the storage modulus of the adhesive layer after photocuring tends to increase. From the viewpoint of reducing the storage modulus of the adhesive layer 2, the total amount of the hydroxyl group-containing monomer and the carboxyl group-containing monomer relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, even more preferably 10 parts by weight or less, and may be 7 parts by weight or less or 5 parts by weight or less.

[0053] The acrylic base polymer contains a nitrogen atom-containing monomer as a constituent monomer component. Nitrogen atom-containing monomers have high polarity and cohesive strength, and the glass transition temperature of the homopolymer is high. Therefore, when the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, the adhesive strength of the pressure-sensitive adhesive layer after photocuring at high temperatures tends to be improved.

[0054] Examples of the nitrogen atom-containing monomer include N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-acryloylmorpholine, N-vinylcarboxylic acid amides, N-vinylcaprolactam, etc. Among these, N-vinylpyrrolidone is particularly preferred because it has a high cohesive force and contributes greatly to improving the adhesive strength at high temperatures.

[0055] From the viewpoint of increasing the adhesive strength of the photocured pressure-sensitive adhesive layer at high temperatures, the amount of the nitrogen atom-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more, based on 100 parts by weight of the total amount of the monomer components constituting the polymer. Even a small amount of the nitrogen atom-containing monomer can contribute to the improvement of the adhesive strength at high temperatures.

[0056] When the amount of the nitrogen atom-containing monomer in the constituent monomer components of the acrylic base polymer is large, the cohesive strength of the base polymer is high, and the glass transition temperature of the adhesive layer tends to be high, and the storage modulus of the adhesive layer after photocuring tends to be large accordingly. In addition, when the amount of the nitrogen atom-containing monomer is large, the adhesive strength of the adhesive layer 2 before photocuring is high, and peeling of the reinforcing film from the adherend tends to be difficult, and this tendency is particularly noticeable for adherends that have been subjected to surface activation treatment such as plasma treatment. From the viewpoint of reducing the adhesive strength of the adhesive before photocuring and reducing the storage modulus of the adhesive after photocuring, the amount of the nitrogen atom-containing monomer relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, and may be 5 parts by weight or less or 3 parts by weight or less.

[0057] The acrylic base polymer may contain a monomer component other than the above. The acrylic base polymer may contain, as a monomer component, for example, a vinyl ester monomer, an aromatic vinyl monomer, an epoxy group-containing monomer, a vinyl ether monomer, a sulfo group-containing monomer, a phosphoric acid group-containing monomer, an acid anhydride group-containing monomer, etc.

[0058] From the viewpoint of imparting excellent adhesiveness to the pressure-sensitive adhesive, the glass transition temperature of the acrylic base polymer is preferably −30° C. or lower, more preferably −40° C. or lower, even more preferably −50° C. or lower, and may be −55° C. or lower or −60° C. or lower. The glass transition temperature of the acrylic base polymer is generally −100° C. or higher, and may be −80° C. or higher or −70° C. or higher.

[0059] The glass transition temperature (Tg) is the temperature (peak top temperature) at which the loss tangent tan δ in viscoelasticity measurement is maximized. Instead of the glass transition temperature determined by viscoelasticity measurement, the theoretical glass transition temperature may be used. The theoretical Tg is the glass transition temperature Tg of a homopolymer of the constituent monomer components of a polymer. i and the weight fraction W of each monomer component i It is calculated using the following Fox formula: 1 / Tg=Σ(W i / Tg i )

[0060] Tg is the theoretical glass transition temperature of the polymer (unit: K), W i is the weight fraction of monomer component i (copolymerization ratio by weight), Tg i is the glass transition temperature (unit: K) of a homopolymer of monomer component i. The glass transition temperature of a homopolymer can be determined from the values ​​listed in Polymer Handbook, 3rd Edition (John Wiley & Sons, Inc., 1989). For the glass transition temperature of a homopolymer of a monomer not listed in the above literature, the peak top temperature of tan δ measured by dynamic viscoelasticity measurement can be used.

[0061] The monomer components are polymerized by various known methods such as solution polymerization, emulsion polymerization, and bulk polymerization to obtain an acrylic polymer as a base polymer. From the viewpoint of the balance of properties such as adhesive strength and holding power of the pressure-sensitive adhesive, and from the viewpoint of cost, the solution polymerization method is preferred. As a solvent for solution polymerization, ethyl acetate, toluene, etc. are used. The solution concentration is usually about 20 to 80% by weight. As a polymerization initiator used in solution polymerization, various known ones such as azo-based and peroxide-based initiators can be used. A chain transfer agent may be used to adjust the molecular weight. The reaction temperature is usually about 50 to 80°C, and the reaction time is usually about 1 to 8 hours.

[0062] The weight average molecular weight of the acrylic base polymer is preferably 200,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. The larger the weight average molecular weight of the base polymer, the higher the adhesive strength at high temperatures tends to be. From the viewpoint of improving adhesive strength at high temperatures, the weight average molecular weight of the acrylic base polymer is preferably 1,000,000 or more, more preferably 1,300,000 or more, and may be 1,500,000 or more, 1,600,000 or more, or 1,700,000 or more.

[0063] If the weight-average molecular weight of the base polymer is too large, the storage modulus of the adhesive is large, and the adhesive strength and flexibility tend to decrease.Therefore, the weight-average molecular weight of the acrylic base polymer is preferably 3 million or less, more preferably 2.5 million or less, and may be 2.2 million or less or 2 million or less.When a crosslinked structure is introduced into the base polymer, the molecular weight of the base polymer refers to the molecular weight before the crosslinked structure is introduced.

[0064] (Crosslinking agent) In order to provide the adhesive with an appropriate cohesive strength, develop adhesive strength, and ensure the peelability of the adhesive layer from the adherend before photocuring, it is preferable that a crosslinked structure is introduced into the base polymer. For example, a crosslinked structure is introduced by adding a crosslinking agent to a solution obtained by polymerizing the base polymer, and heating the solution as necessary. The crosslinking agent has two or more crosslinkable functional groups in one molecule. The crosslinking agent may have three or more crosslinkable functional groups in one molecule.

[0065] Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, and metal chelate-based crosslinking agents. These crosslinking agents react with functional groups such as hydroxyl groups and carboxyl groups introduced into the acrylic base polymer to form a crosslinked structure. Isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred because they are highly reactive with the hydroxyl groups and carboxyl groups of the acrylic base polymer and can easily introduce a crosslinked structure.

[0066] As the isocyanate crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule is used. The isocyanate crosslinking agent may have three or more isocyanate groups in one molecule. As the isocyanate crosslinking agent, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / trile diisocyanate; Examples of the isocyanate adduct include a xylylene diisocyanate trimer adduct (e.g., "Takenate D101E" manufactured by Mitsui Chemicals), a trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., "Coronate HL" manufactured by Tosoh), a trimethylolpropane adduct of xylylene diisocyanate (e.g., "Takenate D110N" manufactured by Mitsui Chemicals), and an isocyanurate of hexamethylene diisocyanate (e.g., "Coronate HX" manufactured by Tosoh). As the isocyanate-based crosslinking agent, an isocyanate compound having a biuret group (e.g., "Duranate 24A-100" manufactured by Asahi Kasei) or an isocyanate compound having an allophanate group may be used.

[0067] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule is used. The epoxy crosslinking agent may have three or more or four or more epoxy groups in one molecule. The epoxy group of the epoxy crosslinking agent may be a glycidyl group. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy-based crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase ChemteX, and "Tetrad X" and "Tetrad C" manufactured by Mitsubishi Gas Chemical may be used.

[0068] The amount of the crosslinking agent used may be adjusted appropriately depending on the composition and molecular weight of the acrylic base polymer, and is preferably about 0.01 to 3 parts by weight relative to 100 parts by weight of the acrylic base polymer. The larger the amount of the crosslinking agent, the higher the crosslinking density of the base polymer, and the more appropriate hardness is imparted to the pressure-sensitive adhesive layer before photocuring, the larger the storage modulus, and the more likely it is that adhesive residue on the adherend is suppressed when the reinforcing film is peeled off from the adherend. On the other hand, if the amount of the crosslinking agent is excessively large, the adhesive strength of the pressure-sensitive adhesive layer after photocuring tends to decrease, and the adhesive strength at high temperatures is particularly likely to decrease. From the viewpoint of achieving both low adhesive strength (easy peelability) of the pressure-sensitive adhesive layer before photocuring and high adhesive strength of the pressure-sensitive adhesive layer after photocuring, the amount of the crosslinking agent is more preferably 0.05 to 1.0 parts by weight, more preferably 0.1 to 0.7 parts by weight, and may be 0.15 to 0.6 parts by weight, 0.2 to 0.5 parts by weight, or 0.25 to 0.4 parts by weight relative to 100 parts by weight of the acrylic base polymer.

[0069] (Light hardener) The adhesive composition constituting the adhesive layer 2 contains, in addition to the base polymer, a compound having two or more photopolymerizable functional groups in one molecule as a photocuring agent. The adhesive composition containing the photocuring agent has photocurability, and when photocuring is performed after lamination with an adherend, the adhesive strength with the adherend is improved.

[0070] From the viewpoint of compatibility with the base polymer, the photocuring agent is preferably a liquid at room temperature. The photopolymerizable functional group of the photocuring agent is preferably one that has polymerizability by photoradical reaction. The photocuring agent is preferably a compound having two or more ethylenically unsaturated bonds in one molecule, and polyfunctional (meth)acrylates are preferred because they show appropriate compatibility with the acrylic base polymer.

[0071] In the present invention, a multifunctional (meth)acrylate having no urethane bond and a multifunctional (meth)acrylate having a urethane bond are used in combination as the photocuring agent. That is, the photocurable composition constituting the adhesive layer 2 contains a multifunctional (meth)acrylate having no urethane bond and a multifunctional (meth)acrylate having a urethane bond. Hereinafter, a multifunctional (meth)acrylate having a urethane bond will be referred to as a "urethane (meth)acrylate". Also, a multifunctional (meth)acrylate having no urethane bond may be simply referred to as a "multifunctional (meth)acrylate".

[0072] The polyfunctional (meth)acrylate having no urethane bond is preferably one having an alkylene oxide chain. As described later, the polyfunctional (meth)acrylate having an alkylene oxide chain has a lower compatibility with the acrylic base polymer than the polyfunctional (meth)acrylate having no alkylene oxide chain, and the initial adhesive strength of the pressure-sensitive adhesive layer tends to be reduced by the formation of the WBL.

[0073] Examples of polyfunctional (meth)acrylates having an alkylene oxide chain include compounds (polyalkylene glycol di(meth)acrylates) having (meth)acryloyl groups at both ends of a polyalkylene oxide chain, such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate. The polyfunctional (meth)acrylate having an alkylene oxide chain may be an ester of an alkylene oxide-modified polyol and (meth)acrylic acid. Examples of the ester of an alkylene oxide-modified polyol and (meth)acrylic acid include bisphenol A alkylene oxide-modified di(meth)acrylate, isocyanuric acid alkylene oxide-modified tri(meth)acrylate, trimethylolpropane alkylene oxide-modified tri(meth)acrylate, pentaerythritol alkylene oxide-modified di(meth)acrylate, pentaerythritol alkylene oxide-modified tri(meth)acrylate, and dipentaerythritol alkylene oxide-modified poly(meth)acrylate.

[0074] In the polyfunctional (meth)acrylate containing an alkylene oxide chain, the alkylene oxide is preferably (poly)ethylene oxide or (poly)propylene oxide, and particularly preferably (poly)ethylene oxide. The chain length of the alkylene oxide (the number of repeating units of the alkylene oxide) n is about 1 to 15. When a plurality of alkylene oxide chains are contained in one molecule, the average chain length n is preferably 1 to 15. The (average) chain length n of the alkylene oxide chain may be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. By adjusting the type and chain length of the alkylene oxide, the compatibility with the acrylic base polymer can be adjusted.

[0075] As the photocuring agent, two or more kinds of polyfunctional (meth)acrylates having no urethane bond may be used in combination. For example, a polyfunctional (meth)acrylate having relatively low compatibility with acrylic base polymers and a polyfunctional (meth)acrylate having relatively high compatibility with acrylic base polymers may be used in combination. For example, a polyfunctional (meth)acrylate having no alkylene oxide chain has high compatibility with acrylic base polymers compared to a polyfunctional (meth)acrylate having an alkylene oxide chain.

[0076] Examples of polyfunctional (meth)acrylates having no alkylene oxide chain include esters of polyols and (meth)acrylic acid such as bisphenol A di(meth)acrylate, alkanediol di(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isocyanuric acid tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol poly(meth)acrylate; epoxy (meth)acrylate, and the like.

[0077] From the viewpoint of compatibility with the acrylic base polymer, the molecular weight of the polyfunctional (meth)acrylate as the photocuring agent is preferably 1500 or less, more preferably 1000 or less, and may be 800 or less, 500 or less, or 400 or less. From the viewpoint of achieving both compatibility with the acrylic base polymer and improved adhesive strength after photocuring, the functional group equivalent (g / eq) of the polyfunctional (meth)acrylate is preferably 500 or less, more preferably 400 or less, even more preferably 300 or less, particularly preferably 200 or less, and may be 180 or less, or 160 or less.

[0078] On the other hand, if the functional group equivalent of the polyfunctional (meth)acrylate is too small, the crosslinking density of the adhesive layer after photocuring may increase, resulting in a decrease in adhesiveness. Therefore, the functional group equivalent of the polyfunctional (meth)acrylate is preferably 80 or more, more preferably 100 or more, and may be 120 or more or 130 or more.

[0079] By including a polyfunctional (meth)acrylate having an alkylene oxide chain and a urethane (meth)acrylate as a photocuring agent, the adhesive strength (initial adhesive strength) of the pressure-sensitive adhesive layer before photocuring tends to be small, and the increase in the initial adhesive strength tends to be suppressed even for adherends that have been subjected to a surface activation treatment such as plasma treatment. In addition, by including a urethane (meth)acrylate as a photocuring agent, the adhesive strength of the pressure-sensitive adhesive layer after photocuring, particularly at high temperatures, tends to be large.

[0080] A urethane (meth)acrylate is a compound having one or more urethane bonds and two or more (meth)acryloyl groups in one molecule, and preferably has two or more urethane bonds in one molecule. A urethane (meth)acrylate having two or more urethane bonds is obtained, for example, by reacting a polyisocyanate with a (meth)acrylic compound having a hydroxy group, and the isocyanate group of the polyisocyanate and the hydroxy group of the (meth)acrylic compound are bonded to form a urethane bond.

[0081] The polyisocyanate may be any of aromatic polyisocyanate, alicyclic polyisocyanate, and alicyclic polyisocyanate. Among them, aromatic polyisocyanate and aliphatic polyisocyanate are preferable. As the aromatic polyisocyanate, tolylene diisocyanate (TDI) is particularly preferable. As the tolylene diisocyanate, 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate may be either, or a mixture of the two. As the aliphatic polyisocyanate, hexamethylene diisocyanate (HDI) is particularly preferable.

[0082] The polyisocyanate may be a trifunctional isocyanate having a cyanuric acid skeleton. Examples of the trifunctional isocyanate having a cyanuric acid skeleton include a TDI trimer and an HDI trimer. The polyisocyanate may have a biuret group or an allophanate group.

[0083] The polyisocyanate may be an isocyanate-terminated urethane prepolymer obtained by reacting a polyol with a polyisocyanate. The isocyanate-terminated urethane prepolymer may be a high molecular weight product obtained by reacting a high molecular weight polyol such as a polyester polyol, a polycarbonate polyol, or a polyether polyol with a polyisocyanate.

[0084] Examples of the (meth)acrylic compound having a hydroxy group include compounds having one hydroxy group and one (meth)acryloyl group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxymethylacrylamide, and hydroxyethylacrylamide; and compounds having one hydroxy group and two or more (meth)acryloyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, and isocyanuric acid di(meth)acrylate.

[0085] Among these, as the (meth)acrylic compound having a hydroxy group, a compound having one hydroxy group and two or more (meth)acryloyl groups is preferable, and specific examples thereof include compounds having a pentaerythritol skeleton such as pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.

[0086] A urethane (meth)acrylate obtained by reacting a diisocyanate with a (meth)acrylic compound having one hydroxyl group and two or more (meth)acryloyl groups in one molecule has two urethane bonds and four or more (meth)acryloyl groups in one molecule. The number of (meth)acryloyl groups in the urethane (meth)acrylate may be 6 or more or 8 or more, or 12 or less or 10 or less.

[0087] The above urethane (meth)acrylate may be commercially available from Kyoeisha Chemical, Shin-Nakamura Chemical, Negami Chemical Industries, Mitsubishi Chemical, Daicel-Allnex, Resonac, or the like.

[0088] From the viewpoint of compatibility with the acrylic base polymer and adjustment of the adhesive strength of the pressure-sensitive adhesive layer, the molecular weight of the urethane (meth)acrylate is preferably 300 to 10,000, more preferably 500 to 2,000, and may be 600 to 1,500, or 700 to 1,200. From the same viewpoint, the functional group equivalent (g / eq) of the (meth)acryloyl group of the urethane (meth)acrylate is preferably 80 to 5,000, more preferably 90 to 1,000, and further preferably 100 to 300, and may be 110 to 250, or 120 to 200.

[0089] The content of the photocuring agent in the pressure-sensitive adhesive composition (the total of the polyfunctional (meth)acrylate having no urethane bond and the urethane (meth)acrylate) is preferably 3 parts by weight or more, more preferably 5 parts by weight or more, even more preferably 7 parts by weight or more, and may be 8 parts by weight or more or 10 parts by weight or more, relative to 100 parts by weight of the acrylic base polymer. By setting the blending amount of the photocuring agent within the above range, a reinforcing film is obtained that is easy to peel from the adherend before photocuring and can be firmly adhered to the adherend by photocuring.

[0090] The larger the amount of the photocuring agent, the smaller the adhesive strength between the adhesive and the adherend before photocuring, and the better the peelability. On the other hand, if the amount of the photocuring agent is excessively large, the photocuring agent is likely to bleed out, and when the reinforcing film is peeled off from the adherend, the bleed-out components may transfer to the adherend, causing contamination. In addition, if the amount of the photocuring agent is excessively large, the adhesive after photocuring tends to have low viscosity and insufficient adhesive strength and flexibility. Therefore, the content of the photocuring agent is preferably 40 parts by weight or less, more preferably 30 parts by weight or less, even more preferably 25 parts by weight or less, and may be 20 parts by weight or less or 15 parts by weight or less, relative to 100 parts by weight of the base polymer.

[0091] From the viewpoint of adjusting the adhesion between the pressure-sensitive adhesive layer and the adherend before and after photocuring to an appropriate range, the content of the polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond is preferably 3 to 30 parts by weight, more preferably 4 to 25 parts by weight, and even more preferably 5 to 20 parts by weight, and may be 6 to 15 parts by weight, 7 to 13 parts by weight, or 8 to 12 parts by weight, relative to 100 parts by weight of the acrylic base polymer.

[0092] From the viewpoint of adjusting the adhesion between the pressure-sensitive adhesive layer and the adherend before and after photocuring to an appropriate range, the content of the urethane (meth)acrylate is preferably 0.03 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and even more preferably 0.08 to 3 parts by weight, and may be 0.1 to 2.5 parts by weight or 0.15 to 2 parts by weight, relative to 100 parts by weight of the acrylic base polymer.

[0093] Multifunctional (meth)acrylates having an alkylene oxide chain have a lower compatibility with acrylic-based polymers than multifunctional (meth)acrylates not having an alkylene oxide chain, and therefore, multifunctional (meth)acrylates having an alkylene oxide chain tend to be unevenly distributed on the surface of the adhesive layer (near the adhesive interface with the adherend), and the light curing agent unevenly distributed on the adhesive interface with the adherend tends to form a Weak Boundary Layer (WBL).

[0094] When a WBL is formed, the adhesive layer retains its bulk properties such as storage modulus, but the liquid properties of the surface (adhesive interface) become stronger, so the adhesive strength with the adherend tends to decrease. Therefore, the adhesive layer before photocuring is easy to peel off from the adherend. When an adhesive layer in which a WBL has been formed with the photocuring agent unevenly distributed near the adhesive interface with the adherend is photocured, the curing reaction of the photocuring agent is likely to proceed near the adhesive interface where the density of the photocuring agent is high, so the adhesive strength tends to increase. In addition, when a WBL is formed, the increase in the storage modulus, which is a bulk property, tends to be suppressed in the adhesive after photocuring.

[0095] By including urethane (meth)acrylate as a photocuring agent in addition to a polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond, the adhesive strength of the pressure-sensitive adhesive layer before photocuring tends to be reduced. One reason for this is thought to be the promotion of WBL formation by the combined use of urethane (meth)acrylate and a polyfunctional (meth)acrylate having no urethane bond, particularly a polyfunctional (meth)acrylate having an alkylene oxide chain.

[0096] When the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, the initial adhesive strength to an adherend that has been surface-activated tends to be large, but when the polymer contains urethane (meth)acrylate as a photocuring agent, the increase in the initial adhesive strength to an adherend that has been surface-activated tends to be suppressed. This is thought to be due to the fact that, in addition to the promotion of WBL formation by urethane (meth)acrylate, the urethane (meth)acrylate present near the adhesive interface with the adherend acts to reduce the interaction between the adherend and the acrylic base polymer.

[0097] Adherends that have been surface-activated by plasma treatment or the like contain many active groups such as hydroxyl groups, carbonyl groups, and carboxyl groups, and have strong intermolecular interactions with the nitrogen atoms of the base polymer of the adhesive, so that the adhesive strength is likely to increase. In particular, when the adherend is a polyimide, polar groups such as amide acid, terminal amino groups, and carboxyl groups (or carboxylic anhydride groups) are activated by the activation treatment, which has strong interactions with the nitrogen atoms of the acrylic base polymer, and the initial adhesive strength is likely to increase by the activation treatment.

[0098] When urethane (meth)acrylate is present as a photocuring agent near the adhesive interface with the adherend, the NH and CO of the urethane bond are likely to form intermolecular interactions with the polar groups of the adherend through hydrogen bonds, etc., and it is believed that the interaction between the acrylic-based polymer and the adherend is relatively weakened. In the adhesive layer before photocuring, the urethane (meth)acrylate as a photocuring agent is liquid and does not have high cohesive strength like the acrylic-based polymer containing nitrogen atoms, so even if the urethane (meth)acrylate forms an intermolecular interaction with the adherend, the adhesive strength hardly increases.

[0099] On the other hand, in the adhesive layer after photocuring, the acrylic base polymer having a crosslinked structure and the polymer formed by the curing of the photocuring agent form a polymer network, so that the nitrogen atoms of the acrylic base polymer and the nitrogen atoms of the urethane (meth)acrylate strongly interact with the adherend. Therefore, it is considered that the adhesive strength between the adhesive layer after photocuring and the adherend at high temperatures is increased by including nitrogen atoms in the acrylic base polymer and including urethane (meth)acrylate as the photocuring agent.

[0100] (Photopolymerization initiator) The photopolymerization initiator generates active species when irradiated with active light rays, and promotes the curing reaction of the photocuring agent. As the photopolymerization initiator, it is preferable to use a photoradical polymerization initiator (photoradical generator).

[0101] The photo-radical polymerization initiator is preferably one that generates radicals upon irradiation with visible light or ultraviolet light having a wavelength shorter than 450 nm, and examples of such initiators include hydroxyketones, benzyl dimethyl ketals, aminoketones, acylphosphine oxides, benzophenones, trichloromethyl group-containing triazine derivatives, etc. The photo-polymerization initiator may be used alone or in combination of two or more.

[0102] The content of the photopolymerization initiator in the pressure-sensitive adhesive layer 2 is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, and even more preferably 0.03 to 2 parts by weight, relative to 100 parts by weight of the base polymer. The content of the photopolymerization initiator in the pressure-sensitive adhesive layer 2 is preferably 0.02 to 20 parts by weight, more preferably 0.05 to 10 parts by weight, and even more preferably 0.1 to 7 parts by weight, relative to 100 parts by weight of the photocuring agent.

[0103] <Other ingredients> As described above, the photocurable adhesive composition constituting the adhesive layer 2 contains an acrylic-based polymer, a photocuring agent, and a photopolymerization initiator. The adhesive composition may contain other components besides these.

[0104] For example, the pressure-sensitive adhesive composition may contain an oligomer having a lower molecular weight than the base polymer. For example, the pressure-sensitive adhesive composition may contain an acrylic oligomer having a weight average molecular weight of about 1,000 to 30,000 in addition to the acrylic base polymer.

[0105] In addition to the above-mentioned components, the pressure-sensitive adhesive composition may contain additives such as a silane coupling agent, a tackifier, a crosslinking accelerator, a crosslinking retarder, a plasticizer, a softener, an antioxidant, an antidegradant, a filler, a colorant, an ultraviolet absorber, a surfactant, and an antistatic agent, within the range that does not impair the characteristics of the present invention.

[0106] Examples of the crosslinking accelerator (crosslinking catalyst) include organometallic compounds such as organometallic complexes (chelates), compounds of metals and alkoxy groups, and compounds of metals and acyloxy groups; and tertiary amines. From the viewpoint of suppressing the progress of the crosslinking reaction in a solution state at room temperature and ensuring the pot life of the adhesive composition, organometallic compounds are preferred. In addition, organometallic compounds that are liquid at room temperature are preferred as crosslinking accelerators, since they are easy to introduce a uniform crosslinked structure throughout the thickness direction of the adhesive layer. Examples of the metal of the organometallic compound include iron, tin, aluminum, zirconium, zinc, titanium, lead, cobalt, zinc, etc.

[0107] Examples of the crosslinking retarder include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate; β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone; and alcohols such as tert-butyl alcohol.

[0108] [Preparation of reinforcing film] A reinforcing film is obtained by laminating a photocurable pressure-sensitive adhesive layer 2 on a film substrate 1. The pressure-sensitive adhesive layer 2 may be formed directly on the film substrate 1, or a pressure-sensitive adhesive layer formed in a sheet form on another substrate may be transferred onto the film substrate 1.

[0109] The above-mentioned adhesive composition is applied to a substrate by roll coating, kiss roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, die coating, or the like, and the solvent is dried and removed as necessary to form an adhesive layer. As the drying method, an appropriate method may be adopted as appropriate. The heating and drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and even more preferably 70°C to 170°C. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and even more preferably 10 seconds to 10 minutes.

[0110] When the pressure-sensitive adhesive composition contains a crosslinking agent, it is preferable to proceed with crosslinking by heating or aging simultaneously with or after drying of the solvent. The heating temperature and heating time are appropriately set depending on the type of crosslinking agent used, and crosslinking is usually performed by heating in the range of 20°C to 160°C for about 1 minute to 7 days. The heating for drying and removing the solvent may also serve as the heating for crosslinking.

[0111] Even after the crosslinking structure is introduced into the polymer by the crosslinking agent, the photocuring agent remains unreacted. Therefore, the adhesive layer 2 is made of a photocurable adhesive composition containing an acrylic base polymer with a crosslinking structure introduced therein, a photocuring agent, and a photopolymerization initiator. When the adhesive layer 2 is formed on the film substrate 1, it is preferable to provide a release liner 5 on the adhesive layer 2 for the purpose of protecting the adhesive layer 2, etc. Crosslinking may be performed after providing the release liner 5 on the adhesive layer 2.

[0112] When the pressure-sensitive adhesive layer 2 is formed on another substrate, the solvent is dried, and then the pressure-sensitive adhesive layer 2 is transferred onto the film substrate 1 to obtain a reinforcing film. The substrate used to form the pressure-sensitive adhesive layer may be used as the release liner 5 as it is.

[0113] As the release liner 5, a plastic film such as polyethylene, polypropylene, polyethylene terephthalate, or polyester film is preferably used. The thickness of the release liner is usually 3 to 200 μm, preferably about 10 to 100 μm. The surface of the release liner 5 that comes into contact with the adhesive layer 2 is preferably subjected to a release treatment using a release agent such as a silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release agent, or silica powder. By subjecting the surface of the release liner 5 to a release treatment, when the release liner 5 is peeled from the film substrate 1, peeling occurs at the interface between the adhesive layer 2 and the release liner 5, and the adhesive layer 2 is maintained in a state of being fixed to the film substrate 1. The release liner 5 may be subjected to an antistatic treatment on either or both of the release-treated surface and the non-treated surface. By subjecting the release liner 5 to an antistatic treatment, charging when the release liner is peeled from the adhesive layer can be suppressed.

[0114] [Characteristics of and use of reinforcing film] The reinforced film of the present invention is used by being attached to a device or a device component. The reinforced film 10 has an adhesive layer 2 fixed to a film substrate 1, and has a low adhesive strength to an adherend before being photocured after being attached to the adherend. Therefore, the reinforced film is easy to peel off from the adherend before being photocured.

[0115] The adherend to which the reinforcing film is attached is not particularly limited, and examples thereof include various electronic devices, optical devices, and components thereof. In one embodiment, the reinforcing film is attached to the surface of a foldable flexible device. The foldable device has a hinge portion and can be folded around this hinge portion. The folding angle can be set arbitrarily, and the device may be bent (folded) at 180°. When the device is a display device, the reinforcing film may be attached to the surface on the screen side, or the reinforcing film may be attached to the back side (housing). In a flexible device that is configured to be bendable at a predetermined location such as a hinge portion, bending and stretching are repeatedly performed at the same location when the device is in use.

[0116] The reinforcing film may be attached to the entire surface of the adherend, or may be selectively attached only to the portion requiring reinforcement (reinforcement target area). After the reinforcing film is attached to the entire portion requiring reinforcement (reinforcement target area) and the area not requiring reinforcement (non-reinforcement target area), the reinforcing film is cut and peeled off from the non-reinforcement target area to produce a device in which the reinforcing film is attached only to the reinforcement target area. Before the adhesive is photocured, the reinforcing film is temporarily attached to the surface of the adherend, and the adhesive strength is small, so the reinforcing film can be easily peeled off and removed from the surface of the adherend.

[0117] By laminating the reinforcing film, appropriate rigidity is imparted, and therefore, it is expected to improve the handling property and prevent damage to thin members such as flexible devices. When the reinforcing film is laminated to a work-in-progress in the device manufacturing process, the reinforcing film may be laminated to a large-sized work-in-progress before being cut to the product size. The reinforcing film may be laminated to a mother roll of a device manufactured by a roll-to-roll process by roll-to-roll.

[0118] For example, a reinforcing film is laminated to a mother roll of a device or a work-in-progress thereof by roll-to-roll, and then the mother roll to which the reinforcing film is laminated is cut and separated into individual products, and only the reinforcing film is cut by half-cutting, and the reinforcing film in the non-reinforcement target area is peeled off to obtain a device in which the reinforcing film is laminated to the reinforcement target area. The cutting method is not particularly limited, and any appropriate cutting method such as a rotary cutter, a push-in blade (e.g., a Thomson blade), or a laser cutter can be used.

[0119] Before laminating the reinforcing film, the surface of the adherend may be activated for the purpose of cleaning, etc. Examples of the surface activation treatment include plasma treatment, corona treatment, and glow discharge treatment. As described above, by including urethane (meth)acrylate as a photocuring agent, even if the acrylic base polymer includes nitrogen atoms, an excessive increase in the initial adhesive strength to an adherend whose surface has been activated can be suppressed. The adhesive strength F1 between the adherend that has been subjected to the surface activation treatment and the pressure-sensitive adhesive layer before photocuring is preferably 1.4 times or less, and may be 1.3 times or less, or 1.2 times or less, of the adhesive strength F0 between the adherend that has not been subjected to the surface activation treatment and the pressure-sensitive adhesive layer before photocuring.

[0120] From the viewpoint of facilitating peeling from the adherend and preventing adhesive residue on the adherend after peeling of the reinforcing film, the adhesive strength (initial adhesive strength) between the adhesive layer 2 and the adherend before photocuring is preferably 0.5 N / 25 mm or less, more preferably 0.4 N / 25 mm or less, even more preferably 0.3 N / 25 mm or less, and may be 0.25 N / 25 mm or less or 0.2 N / 25 mm or less. From the viewpoint of preventing peeling of the reinforcing film during storage or handling, the adhesive strength between the adhesive layer 2 and the adherend before photocuring is preferably 0.005 N / 25 mm or more, more preferably 0.01 N / 25 mm or more.

[0121] The adhesive strength is determined by a peel test using a polyimide film as the adherend, with a tensile speed of 300 mm / min and a peel angle of 180°. Unless otherwise specified, the adhesive strength is measured at 25°C. The adhesive strength between the pressure-sensitive adhesive layer and the adherend before photocuring is measured using a sample that has been left to stand at 25°C for 30 minutes after lamination.

[0122] From the viewpoint of facilitating peeling of the reinforcing film from the plasma-treated adherend, the adhesive layer of the reinforcing film preferably has an adhesive strength F1 at a temperature of 25° C. in the above range before photocuring to a plasma-treated polyimide film. The adhesive strength F0 of the adhesive layer at a temperature of 25° C. before photocuring to a polyimide film that has not been subjected to a surface activation treatment such as plasma treatment is preferably 0.4 N / 25 mm or less, more preferably 0.35 N / 25 mm or less, even more preferably 0.3 N / 25 mm or less, and may be 0.25 N / 25 mm or less or 0.2 N / 25 mm or less. As mentioned above, F1 / F0 is preferably 1.4 or less, and may be 1.3 or less or 1.2 or less.

[0123] The shear storage modulus of the pressure-sensitive adhesive layer 2 at a temperature of 25° C. before photocuring (hereinafter simply referred to as “storage modulus”) is preferably 15 kPa or more, more preferably 20 kPa or more, and may be 25 kPa or more or 30 kPa or more. The greater the storage modulus of the pressure-sensitive adhesive layer at room temperature before photocuring, the more improved the cutting processability is, and the more likely it is that adhesive residue on the adherend is suppressed when the reinforcing film is peeled off from the adherend.

[0124] On the other hand, if the storage modulus of the adhesive layer at room temperature before photocuring is excessively large, the storage modulus of the adhesive layer after photocuring also tends to be large, and the adhesion to the adherend and impact resistance may be insufficient. In addition, if the storage modulus of the adhesive layer before photocuring is large, the storage modulus of the adhesive layer after photocuring also tends to be large, and when applied to a foldable device, the adhesive layer cannot absorb the strain at the bending point and its surroundings, and the reinforcing film is easily peeled off from the device. Therefore, the storage modulus of the adhesive layer at a temperature of 25°C before photocuring is preferably 60 kPa or less, more preferably 55 kPa or less, even more preferably 50 kPa or less, and may be 45 kPa or less or 40 kPa or less.

[0125] The storage modulus of the pressure-sensitive adhesive layer is determined by reading the value at a predetermined temperature when measured at a temperature rise rate of 5°C / min in the range of -70 to 200°C under a frequency condition of 1 Hz in accordance with the method described in JIS K7244-1 "Plastics - Test method for dynamic mechanical properties." In this specification, the storage modulus is the value at a temperature of 25°C, unless otherwise specified.

[0126] After laminating the reinforcing film to the adherend, the pressure-sensitive adhesive layer 2 is irradiated with active light rays to photocure the pressure-sensitive adhesive layer. The active light rays are preferably ultraviolet rays. The irradiation intensity and irradiation time of the active light rays may be appropriately set depending on the composition and thickness of the pressure-sensitive adhesive layer 2. The pressure-sensitive adhesive layer 2 may be irradiated with active light rays from either the film substrate 1 side or the adherend side, or may be irradiated with active light rays from both sides.

[0127] When the adhesive layer 2 is photocured, the photocuring agent undergoes a curing reaction, and the adhesive strength with the adherend increases. From the viewpoint of adhesive reliability during practical use of the device, the adhesive strength F2 between the adhesive layer and the adherend (plasma-treated polyimide film) after photocuring at a temperature of 25°C is preferably 3N / 25mm or more, more preferably 5N / 25mm or more, and may be 7N / 25mm or more, 9N / 25mm or more, or 10N / 25mm or more. The adhesive strength F2 between the adhesive layer and the adherend after photocuring is preferably 10 times or more, more preferably 15 times or more, even more preferably 20 times or more, and may be 30 times or more, or 50 times or more, of the adhesive strength F1 between the adhesive layer and the adherend before photocuring.

[0128] The adhesive strength F3 between the adhesive layer and the adherend (plasma-treated polyimide film) after photocuring at a temperature of 85° C. is preferably 1 N / 25 mm or more, more preferably 2 N / 25 mm or more, even more preferably 3 N / 25 mm or more, and may be 4 N / 25 mm or more, 5 N / 25 mm or more, or 6 N / 25 mm or more. As described above, the adhesive composition contains an acrylic-based polymer having nitrogen atoms and a urethane (meth)acrylate as a photocuring agent, thereby reducing the initial adhesive strength to an adherend that has been subjected to a surface activation treatment, and achieving high adhesive strength in a high-temperature environment after photocuring.

[0129] From the viewpoint of realizing high adhesive strength with the adherend after photocuring, the storage modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 40 kPa or more, more preferably 50 kPa or more, and may be 55 kPa or more or 60 kPa or more. On the other hand, if the storage modulus of the adhesive layer after photocuring is excessively large, the adhesive strength to the adherend and the impact mitigation effect (cushioning property) tend to decrease. In addition, if the storage modulus of the adhesive layer after photocuring is excessively large, when applied to a foldable device, the reinforcing film is likely to peel off from the device at and around the bending point. Therefore, the storage modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 150 kPa or less, more preferably 120 kPa or less, even more preferably 100 kPa or less, and may be 90 kPa or less or 80 kPa or less.

[0130] The smaller the amount of crosslinking agent and the smaller the amount of photocuring agent, the smaller the storage modulus of the adhesive layer after photocuring tends to be, and the smaller the amount of photocuring agent, the smaller the increase in the storage modulus of the adhesive layer due to photocuring tends to be. In addition, by including a polyfunctional (meth)acrylate and a urethane (meth)acrylate having an alkylene oxide chain and no urethane bond as the photocuring agent, the adhesive strength with the adherend tends to be increased while suppressing the increase in the storage modulus of the adhesive layer due to photocuring.

[0131] By laminating a reinforcing film, appropriate rigidity is imparted to the adherend and stress is alleviated and dispersed, thereby suppressing various defects that may occur during the manufacturing process, improving production efficiency, and increasing yields.

[0132] The reinforcing film of the present invention has a photocurable adhesive layer 2, and the timing of curing can be set as desired. Before the photocuring of the adhesive layer, the reinforcing film of the present invention has a low adhesive strength even to a surface-treated adherend, so that it is easy to peel off from the adherend, and is easy to rework even if lamination or bonding failure occurs. In addition, processing such as selectively removing the reinforcing film from the non-reinforcement target area is also easy.

[0133] After the pressure-sensitive adhesive layer is photocured, it exhibits high adhesive strength to the adherend, and also exhibits high adhesive strength at high temperatures, so that the reinforced film is unlikely to peel off from the device surface. In a device with a reinforced film in which the reinforced film of the present invention is bonded to a flexible device using a resin substrate, even when the device is repeatedly bent, the reinforced film is unlikely to peel off at the bent portion, and the device has excellent adhesion reliability. EXAMPLES

[0134] The present invention will be further explained below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0135] [Preparation of base polymer] <Polymer A> In a reaction vessel equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen gas inlet tube, 20 parts by weight of butyl acrylate (BA), 70 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of lauryl acrylate (LA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA) and 1 part by weight of N-vinyl-2-pyrrolidone (NVP) were charged as monomers, 0.1 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent, and nitrogen gas was introduced and the mixture was substituted with nitrogen for about 1 hour while stirring.Then, the mixture was heated to 60°C and reacted for 7 hours to obtain a solution of acrylic polymer A with a weight average molecular weight of 1.8 million.

[0136] <Polymer B> A solution of acrylic polymer B having a weight average molecular weight of 550,000 was obtained in the same manner as in the polymerization of polymer A, except that the amount of the thermal polymerization initiator (AIBN) was changed to 0.2 parts by weight.

[0137] <Polymers C to E> The amounts of monomers charged were changed as shown in Table 1. Solutions of polymers C to E were obtained in the same manner as in the polymerization of polymers A and B. In the polymerization of polymers C and D, 0.2 parts by weight of a thermal polymerization initiator was used, and in the polymerization of polymer E, 0.1 parts by weight of a thermal polymerization initiator was used.

[0138] The monomer ratios of the acrylic polymers A to E and the weight average molecular weights (Mw) of the polymers are listed in Table 1. The weight average molecular weights (polystyrene equivalent) were measured using GPC (Tosoh's "HLC-8220GPC") under the following conditions. Sample concentration: 0.2% by weight (tetrahydrofuran solution) Sample injection volume: 10 μL Eluent:THF Flow rate: 0.6mL / min Measurement temperature: 40℃ Sample column: TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns) Reference column: TSKgel SuperH-RC (1 column)

[0139] In Table 1, the monomers are described by the following abbreviations. BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate NOAA: n-Octyl acrylate MMA: Methyl methacrylate LA: Lauryl acrylate 2HEA: 2-hydroxyethyl acrylate 4HBA: 4-hydroxybutyl acrylate NVP: N-vinyl-2-pyrrolidone

[0140] [Table 1]

[0141] [Preparation of reinforcing film] <Preparation of Pressure-Sensitive Adhesive Composition> A crosslinking agent, a multifunctional acrylate (having no urethane bond) and a urethane acrylate as a photocuring agent, and a photopolymerization initiator were added to the acrylic polymer solution and mixed uniformly to prepare the pressure-sensitive adhesive composition shown in Table 2.

[0142] As a crosslinking agent, an isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh) was added in the amount shown in Table 2. As a photopolymerization initiator, "Omnirad 651" manufactured by IGM Resins was added in an amount of 0.3 parts by weight per 100 parts by weight of the solid content of the acrylic polymer. The photohardeners (polyfunctional acrylate and urethane acrylate) were added in the amounts shown in Table 2. The amounts added in Table 2 are the amounts (parts by weight of solid content) per 100 parts by weight of the acrylic polymer. Details of the photohardeners are as follows:

[0143] (Multifunctional acrylate) A200: Shin-Nakamura Chemical Co., Ltd. "NK Ester A200" (polyethylene glycol #200 (n=4) diacrylate; molecular weight 308, functional group equivalent 154g / eq) M350: Trimethylolpropane EO modified (n=1) triacrylate (Toagosei "Aronix M-350", functional group equivalent 143g / eq) ADPHE: Ethoxylated dipentaerythritol polyacrylate ("NK Ester A-DPH-12E" manufactured by Shin-Nakamura Chemical Co., Ltd., functional group equivalent weight approx. 200 g / eq) TMPT: Trimethylolpropane triacrylate ("NK Ester A-TMPT" manufactured by Shin-Nakamura Chemical Co., Ltd., functional group equivalent weight 99g / eq)

[0144] (Urethane acrylate) UA306: Pentaerythritol triacrylate-tolylene diisocyanate adduct (Kyoeisha Chemical "UA-306T", functional group equivalent: 128g / eq) UA510: Dipentaerythritol pentaacrylate hexamethylene diisocyanate adduct (Kyoeisha Chemical "UA-510H", functional group equivalent: 181g / eq) UF-X9-83: Polycarbonate skeleton-containing urethane acrylate (Kyoeisha Chemical's "UF-X9-83", functional groups 2-3, weight average molecular weight 8400)

[0145] <Application of adhesive solution and crosslinking> The above adhesive composition was applied to a 50 μm-thick polyethylene terephthalate film substrate (Mitsubishi Chemical's "Diafoil T100") that had not been surface-treated, using a fountain roll, so that the thickness after drying would be 15 μm. After drying at 130° C. for 1 minute to remove the solvent, the release-treated surface of a release liner (a 25 μm-thick polyethylene terephthalate film whose surface was silicone release-treated) was attached to the adhesive-coated surface. Thereafter, aging treatment was performed for 4 days in an atmosphere at 25° C. to promote crosslinking, and a reinforced film was obtained in which an adhesive sheet was fixed and laminated on the film substrate, and a release liner was temporarily attached thereon.

[0146] [evaluation] <Adhesion to polyimide film> (Adhesive strength of adhesive layer before photocuring) A 25 μm thick polyimide film (UBE "Upilex 25S") was attached to a glass plate via double-sided adhesive tape (Nitto Denko "No. 531") to obtain a polyimide film substrate for measurement. The release liner was peeled off and removed from the surface of a reinforcing film cut to a width of 25 mm and a length of 100 mm, and the film was attached to the polyimide film substrate for measurement using a hand roller.

[0147] After leaving this sample at 25°C for 30 minutes, the edge of the film substrate of the reinforcing film was held with a chuck and a 180° peel test was performed at a tensile speed of 300 mm / min to measure the peel strength (adhesion strength F0 of the reinforcing film to the polyimide film without plasma treatment).

[0148] While conveying the polyimide film substrate for measurement at a conveying speed of 3 m / min, a normal pressure plasma treatment machine was used to perform plasma treatment on the surface of the polyimide film under the condition of an electrode voltage of 160 V. A reinforcing film was attached to the plasma-treated polyimide film using a hand roller, and the adhesive strength F1 to the plasma-treated polyimide film was measured by a 180° peel test in the same manner as above.

[0149] From the obtained results, the ratio F1 / F0 of the adhesive strength F1 with plasma treatment to the adhesive strength F0 without plasma treatment was calculated.

[0150] (Adhesive strength of adhesive layer after photocuring) After laminating the reinforcing film to the polyimide film substrate (with plasma treatment) for measurement, an LED light source with a wavelength of 365 nm was used to illuminate the reinforcing film side (film base side) with an integrated light intensity of 4000 mJ / cm. 2The adhesive layer was photocured by irradiating it with ultraviolet light of 180°. The adhesive strength F2 of this test sample was measured by a 180° peel test at a temperature of 25° C. in the same manner as above. Furthermore, the test sample after the adhesive layer was photocured was stored in an oven at a temperature of 85° C. for 5 minutes, and then a 180° peel test was performed in an environment at a temperature of 85° C. to measure the adhesive strength F3.

[0151] <Storage modulus> The adhesive composition was applied and crosslinked on the release liner in the same manner as above to prepare an adhesive sheet (before photocuring). A release liner was attached to the surface of the adhesive layer of the adhesive sheet before photocuring to isolate it from oxygen, and the adhesive sheet was exposed to 4000 mJ / cm 2 with a 365 nm LED lamp. 2 The adhesive sheet before and after photocuring were laminated to prepare a measurement sample having a thickness of about 1.5 mm, and dynamic viscoelasticity measurement was performed under the following conditions using a rotational rheometer ("Discovery-HR2" manufactured by TA Instruments), and the shear storage modulus G' at 25°C was read. (Measurement conditions) Deformation mode: Torsion Measurement frequency: 1Hz Heating rate: 5℃ / min Measurement temperature: -70~200℃ Shape: Parallel plate 8.0mmφ

[0152] <Stainability of adherends> The release liner was peeled off from the surface of the reinforced film cut into a size of 25 mm wide x 100 mm long, and the film was then attached to a polyimide film substrate (not plasma-treated) for measurement using a hand roller. After leaving the film at rest for 30 minutes or 24 hours at 25°C, the reinforced film was peeled off from the polyimide film, and the surface of the polyimide film was visually inspected under a fluorescent lamp to confirm the presence or absence of contamination. The contamination of the adherend was evaluated according to the following criteria. A: No contamination was observed in the sample that was peeled off after being left to stand for 24 hours. B: Contamination was observed in the sample peeled off after leaving it for 24 hours, but not in the sample peeled off after leaving it for 30 minutes. C: Sample that was left standing for 30 minutes and was peeled off, showing signs of contamination

[0153] Table 2 shows the composition of the adhesive for each reinforcing film (type of base polymer, amount of crosslinking agent added, type and amount of photocuring agent added) and the evaluation results.

[0154] [Table 2]

[0155] Comparative Example 1, which used a pressure-sensitive adhesive composition containing 10 parts by weight of a multifunctional acrylate (M350) as a photocuring agent for 100 parts by weight of polymer A, had an adhesive strength F0 to a polyimide film that had not been plasma-treated of more than 0.5 N / 25 mm, indicating a large initial adhesive strength. Also, in Comparative Example 1, the adhesive strength F1 to a polyimide film that had been plasma-treated increased to more than 1.5 times the adhesive strength F0 to a polyimide film that had not been plasma-treated, indicating that the initial adhesive strength had increased significantly due to the plasma treatment of the adherend.

[0156] In Example 1, in which 0.15 parts by weight of urethane acrylate (UA306) was blended in addition to 10 parts by weight of multifunctional acrylate (M350) as the photocuring agent, the adhesive strength F0 to a polyimide film that had not been subjected to plasma treatment was 1 / 3 or less of that in Comparative Example 1. In Example 1, the adhesive strength F1 to a polyimide film that had been subjected to plasma treatment was 1.2 times the adhesive strength F0 to a polyimide film that had not been subjected to plasma treatment, and the increase in the initial adhesive strength due to the plasma treatment of the adherend was suppressed.

[0157] In Example 1, the adhesive strength was significantly increased by photocuring the adhesive, and the adhesive strength was as high as 6 N / 25 mm or more even at a high temperature of 85° C. Furthermore, the storage modulus of the adhesive after photocuring was 70 kPa or less, and in addition to the high adhesive strength, the adhesive had flexibility that makes it applicable to foldable devices and the like.

[0158] Example 16, which used polymer B, which has a lower molecular weight than polymer A, as the base polymer of the adhesive, had low initial adhesive strength regardless of whether the adherend was plasma-treated or not, and showed high adhesive strength to the adherend after photocuring, similar to Example 1. In Example 16, the adhesive after photocuring had a smaller storage modulus and better flexibility than Example 1. On the other hand, Example 16 showed a smaller adhesive strength F3 at high temperatures after photocuring than Example 1.

[0159] Comparative Example 5, which used polymer C, which does not contain a monomer component having a nitrogen atom, as the base polymer of the adhesive, and Comparative Example 7, which used polymer E, both had low initial adhesive strength, and the increase in initial adhesive strength due to plasma treatment of the adherend was suppressed. However, in Comparative Examples 5 and 7, the adhesive had an adhesive strength F3 of less than 1 N / 25 mm at high temperatures after photocuring, and the adhesive reliability was poor.

[0160] Comparing Examples 1 and 16 with Comparative Examples 5 and 7, it can be seen that a reinforcing film having a photocurable adhesive layer containing an acrylic polymer containing nitrogen atoms and a multifunctional (meth)acrylate without a urethane bond and a multifunctional (meth)acrylate with a urethane bond exhibits low initial adhesion even to an activated substrate, and after the adhesive is photocured, exhibits high adhesion to the substrate as well as high adhesion at high temperatures, demonstrating excellent adhesion reliability.

[0161] Comparative Example 6, which used polymer D containing 15 parts by weight of a nitrogen-containing monomer component (NVP) as the base polymer of the adhesive, had high initial adhesive strength, and the adhesive strength increased by 1.4 times or more to an adherend that had been subjected to plasma treatment. This result shows that even when urethane (meth)acrylate is used as the light curing agent, it is difficult to reduce the initial adhesive strength if the acrylic base polymer has a high nitrogen atom content.

[0162] Examples 2 to 4, in which the amount of urethane acrylate (UA306) added was increased compared to Example 1, had a small initial adhesive strength to the adherend, and the increase in initial adhesive strength due to plasma treatment of the adherend was suppressed, similar to Example 1, and further had excellent adhesive strength at high temperatures of the adhesive layer after photocuring. Comparing Examples 1 to 4, there was a tendency that the greater the amount of urethane acrylate added, the smaller the initial adhesive strength was and the higher the adhesive strength at high temperatures of the adhesive layer after photocuring.

[0163] Examples 12 and 13, which used a urethane acrylate different from that of Example 1, had a small initial adhesive strength, and the increase in initial adhesive strength due to plasma treatment was suppressed, similar to Example 1, and further had excellent adhesive strength at high temperatures of the adhesive layer after photocuring. These results show that the urethane acrylate contributes to the reduction in initial adhesive strength and the increase in adhesive strength at high temperatures of the adhesive layer after photocuring.

[0164] In Examples 3 and 4, in which the amount of urethane acrylate was increased, the initial adhesive strength was lower and the peelability was good compared to Examples 1 and 2, but contamination of the adherend was observed when the reinforcing film was peeled off before the adhesive was photocured. The cause of contamination is thought to be the excess photocuring agent bleeding out onto the surface of the adhesive layer and transferring to the adherend.

[0165] Example 12, which used a 10-functional urethane acrylate (UA510), had a smaller initial adhesive strength than Example 1, which used a 6-functional urethane acrylate (UA306), and the adhesive strength at high temperatures after photocuring was greater. On the other hand, Example 13, which used a high molecular weight urethane acrylate (UF-X9-83), had a larger initial adhesive strength than Examples 1 and 10, and the adhesive strength at high temperatures after photocuring was smaller. These results show that the greater the number of functional groups in the urethane acrylate and the smaller the functional group equivalent, the greater the effect of reducing the initial adhesive strength and improving the adhesive strength at high temperatures.

[0166] In Examples 14 and 15, in which the type of multifunctional acrylate without urethane bonds was changed, the initial adhesive strength to the adherend was small, the increase in the initial adhesive strength due to plasma treatment of the adherend was suppressed, and the adhesive strength at high temperatures after photocuring was also excellent, as in Example 1. On the other hand, in Comparative Example 4, in which TMPT, a multifunctional acrylate without an alkylene oxide chain, was used, the initial adhesive strength was high, and the adhesive strength hardly increased even when the adhesive was photocured. From these results, it can be seen that by using a urethane (meth)acrylate and a multifunctional (meth)acrylate having an alkylene oxide chain as a photocuring agent, it is possible to achieve both a reduction in the initial adhesive strength and an improvement in the adhesive strength at high temperatures.

[0167] In Comparative Example 2, in which the amount of the polyfunctional acrylate (M350) having an alkylene oxide chain was 2 parts by weight, the initial adhesive strength was high, and the adhesive strength at high temperatures after photocuring was insufficient. Comparing Examples 1, 8, and 9, in which the amount of the polyfunctional (meth)acrylate was changed, there was a tendency that the initial adhesive strength was smaller and the adhesive strength at high temperatures after photocuring was larger as the amount of the polyfunctional acrylate was larger.

[0168] On the other hand, in Examples 10 and 11, in which the amount of the multifunctional acrylate was further increased from that of Example 1, the initial adhesive strength decreased with an increase in the amount of the multifunctional acrylate, but the adhesive strength after photocuring also tended to decrease. Furthermore, in Examples 10 and 11, the storage modulus of the adhesive layer after photocuring was larger than that of Example 1, and contamination of the adherend was observed when the reinforcing film was peeled off before the photocuring of the adhesive. In Comparative Example 3, in which the amount of the multifunctional acrylate was further increased, the adhesive strength of the adhesive after photocuring was low at less than 1 N / 25 mm, and the storage modulus exceeded 150 kPa.

[0169] These results show that, although increasing the amount of photocuring agent tends to reduce the initial adhesive strength and increase the adhesive strength after photocuring, if the amount of photocuring agent is too high, the adhesive becomes hard after photocuring and loses its viscosity, making it impossible to achieve high adhesive strength.

[0170] Comparing Example 1 with Examples 5 to 7, there was a tendency that the adhesive strength of the pressure-sensitive adhesive layer before and after photocuring decreased and the storage modulus increased as the amount of crosslinking agent increased.

[0171] From the above results, it can be seen that a reinforcing film having a photocurable adhesive layer containing an acrylic polymer containing nitrogen atoms and a multifunctional (meth)acrylate without a urethane bond and a multifunctional (meth)acrylate with a urethane bond exhibits low initial adhesion even to an activated substrate, and after the adhesive is photocured, exhibits high adhesion to the substrate as well as high adhesion at high temperatures, demonstrating excellent adhesion reliability. [Explanation of symbols]

[0172] 1 Film substrate 2 Adhesive layer 10 Reinforcement film 5 Release Liner 20 Adherent

Claims

1. The adhesive tape comprises a film substrate and a pressure-sensitive adhesive layer fixedly laminated on one main surface of the film substrate, the pressure-sensitive adhesive layer is made of a photocurable composition including an acrylic base polymer, a photocuring agent having two or more photopolymerizable functional groups, and a photopolymerization initiator; The acrylic base polymer contains, as monomer components, at least one selected from the group consisting of a hydroxy group-containing monomer and a carboxy group-containing monomer, and a nitrogen atom-containing monomer; A crosslinked structure is introduced into the acrylic base polymer, the content of the nitrogen atom-containing monomer is 0.3 to 10 parts by weight based on 100 parts by weight of the total amount of the monomer components of the acrylic base polymer; The photocurable composition contains, as the photocuring agent, 3 to 30 parts by weight of a polyfunctional (meth)acrylate having an alkylene oxide chain and no urethane bond, relative to 100 parts by weight of the acrylic base polymer; and 0.03 to 5 parts by weight of a urethane (meth)acrylate, relative to 100 parts by weight of the acrylic base polymer. Reinforcement film.

2. The reinforcing film according to claim 1, wherein a crosslinked structure is introduced into the acrylic base polymer using 0.05 to 1.0 parts by weight of a crosslinking agent relative to 100 parts by weight of the polymer.

3. The reinforced film according to claim 2 , wherein the crosslinking agent is an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent.

4. The reinforcing film according to claim 1, wherein the polyfunctional (meth)acrylate has a functional group equivalent of a (meth)acryloyl group of 80 to 500 g / eq.

5. The reinforcing film according to claim 1, wherein the urethane (meth)acrylate has a functional group equivalent of a (meth)acryloyl group of 80 to 5000 g / eq.

6. The reinforcing film according to claim 1 , wherein the urethane (meth)acrylate has four or more (meth)acryloyl groups in one molecule.

7. The pressure-sensitive adhesive layer is Before photocuring, the adhesive strength F to the polyimide film at a temperature of 25° C. 0 is 0.4 N / 25 mm or less, and the adhesive strength F 1 But, F 0 is 1.4 times or less, After photocuring, the adhesive strength F to the plasma-treated polyimide film in an environment at a temperature of 25° C. 2 Adhesive strength F at 3.0 N / 25 mm or more and at a temperature of 85°C 3 is 1.0N / 25mm or more, The reinforced film according to claim 1 .

8. The reinforcing film according to claim 1 , wherein the pressure-sensitive adhesive layer has a shear storage modulus of 150 kPa or less at a temperature of 25° C. after photocuring.

9. A method for manufacturing a device having a reinforcing film bonded to a surface thereof, comprising the steps of: After the pressure-sensitive adhesive layer of the reinforcing film according to any one of claims 1 to 8 is temporarily attached to the surface of an adherend, A device manufacturing method comprising: irradiating the pressure-sensitive adhesive layer with active light rays to photocure the pressure-sensitive adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.

10. The method for manufacturing a device described in claim 9, wherein after the reinforcing film is temporarily attached to the adherend, and before the adhesive layer is photocured, the reinforcing film temporarily attached to the adherend is cut, and the reinforcing film is peeled off and removed from a portion of the adherend.

11. The method for producing a device according to claim 9 , wherein a surface activation treatment is performed on the adherend before the reinforcing film is temporarily attached.

12. The method for manufacturing a device according to claim 11 , wherein the surface activation treatment is a plasma treatment.

13. The method for manufacturing a device according to claim 9 , wherein the adherend comprises a polyimide film, and the pressure-sensitive adhesive layer of the reinforcing film is attached to the polyimide film.

14. The method for manufacturing a device according to claim 9 , wherein the adherend is a foldable image display element.

15. A reinforcing method for bonding a reinforcing film to a surface of an adherend, comprising the steps of: The pressure-sensitive adhesive layer of the reinforcing film according to any one of claims 1 to 8 is temporarily attached to a surface of an adherend, The reinforcing method includes irradiating the pressure-sensitive adhesive layer with active light rays to photocure the pressure-sensitive adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.

Citation Information

Patent Citations

  • Reinforcement film, manufacturing method of device, and reinforcement method

    JP2020132846A